An agent-based modeling and simulation for the first stage of honeycomb construction. Issue 1 (1st March 2022) - Narumi, Takayuki; Akiyama, Takumi; Kageyama, Maya; Uemichi, Kenta; Honda, Hisao; Osaki, Koichi
Abstract: Honeybees construct nests that consist of well-arrayed cells. In the first stage of honeycomb construction, they build a linear sequence of tetrapod structures that form the basis of the honeycomb. However, it is unknown how honeybees produce that initial pattern. To understand the mechanisms of honeycomb construction, we proposed an agent-based model, the attachment-excavation model, in which worker honeybees are classified into attachers and excavators. Simulation results showed that a tripod pattern emerges due to competition between the attachers and excavators. As time advances, isotropic wax growth causes the tripods to spread concentrically. We then employed anisotropic wax growth to obtain a linear sequence of constructed tripods. In the present paper, we discuss the origin of the anisotropy based on experimental results.